Thermodynamic Destabilisation of MgH2 and NaMgH3 using Group IV elements Si, Ge and Sn - Chaudhary, Anna-Lisa; Paskevicius, Mark; Sheppard, Drew; Buckley, Craig (Elsevier B.V., 2015)
The addition of Group IV elements of Si, Ge or Sn to Mg-based hydrides has led to the successful destabilisation of MgH2 or NaMgH3, resulting in hydrogen release at lower temperatures. This is the first time a direct comparison has been made with all the samples prepared and characterised using identical conditions. Pure MgH2 desorbs hydrogen at a pressure of 1 bar at 282 °C, a temperature too high for typical mobile applications. The addition of Group IV metals to MgH2 causes the formation of intermetallic compounds (Mg2Si, Mg2Ge and Mg2Sn) upon hydrogen release. Theoretical calculations show promising thermodynamic equilibrium conditions for these systems. Experimentally, these conditions were difficult to achieve, however, hydrogen desorption results show that Ge has the most significant effect in allowing low temperature hydrogen release, followed by Sn, then Si. It was found that Si also has a beneficial effect on NaMgH3, reducing the desorption temperature.